VD_FINDINFO HC / 2022 / 553 vom 8. Juli 2022 - VD Tribunal cantonal (2022)
CUMUL D'ACTIONS, BONNE FOI SUBJECTIVE, DROIT D'ÊTRE ENTENDU, COMPÉTENCE RATIONE MATERIAE | 107 ch. 4 CRF, 52 CPC (CH), 53 al. 1 CPC (CH), 90 CPC (CH)